Pemberdayaan Mandiri Karang Taruna Dalam Inovasi Kerajinan Bambu Hutan Adat Temedak untuk Meningkatkan Keterampilan Pemuda Desa Kabupaten Kerinci - Anggi Desviana Siregar; Ravico Ravico; Reri Seprina Anggraini; Rhomiy Handican; Rian Rafiska (Rengganis Jurnal Pengabdian Masyarakat, 2022)
The purpose of this service activity is to develop skills for youth villager who are involved in Karang Taruna in managing natural products in the Temedak Customary forest, Keluru Village, Kerinci Regency, Jambi Province. One of the many natural products found in the Temedak customary forest is Forest Bamboo which can be managed by the surrounding community. This mentoring activity was carried out with the support of the government and BumDes, the surrounding community and the assistance of IAIN Kerinci's Kukerta Students. In addition, this service is expected to provide knowledge in several fields, namely production, sales promotion, and marketing of a product. The method used is the guidance and evaluation method. The results of innovations made by youth organizations by processing bamboo into products that have selling and innovative values such as decorative lamps, tissue holders, and others.